Plantar vein thrombosis and pulmonary embolism. (February 2015) - Barros, MVL; Nascimento, IS; Barros, TLS; Labropoulos, N
Plantar vein thrombosis is an unusual and under-diagnosed condition that affects the plantar deep venous system. Current ultrasound investigation protocols for deep venous thrombosis neglect this entity. To our knowledge, there are only seven reports in the literature of 20 patients with plantar vein thrombosis detected with sonography without an associated pulmonary embolism. We present a case report of a patient with a plantar vein thrombosis associated with pulmonary embolism. Patients who present with pain and/or swelling of the foot should undergo ultrasound examination and careful evaluation for respiratory symptoms.